2008
DOI: 10.1007/s12195-008-0035-5
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Characterization by Surface Plasmon Resonance-Based Biosensors: Principle and Emerging Trends

Abstract: Within the last three decades, surface plasmon resonance (SPR)-based optical biosensors have emerged as leading instruments for the study of biomolecular interactions. The rapid dissemination of the technology has provided researchers with versatile and sensitive instruments for the identification of kinetic and thermodynamic parameters related to macromolecular interactions. This review article presents the basic principles, as well as the classical experimental approaches and data treatment techniques relate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 64 publications
0
42
0
Order By: Relevance
“…This year it was De Crescenzo et al's turn (6). They reviewed the physics of SPR, described Biacore's dextran layer, outlined methods to reduce experimental artefacts (e.g.…”
Section: Roll Callmentioning
confidence: 99%
“…This year it was De Crescenzo et al's turn (6). They reviewed the physics of SPR, described Biacore's dextran layer, outlined methods to reduce experimental artefacts (e.g.…”
Section: Roll Callmentioning
confidence: 99%
“…SPR has established itself as a powerful technique for providing affinity and kinetic information of target-based biomolecular interactions [29], [30]. However, several studies have demonstrated that SPR is also a powerful tool for real-time monitoring of living cell interactions, and for studying different cellular processes without the use of labeling agents [15], [16], [18], [19][22], [24], [26]., So far all SPR interaction studies with living cells are performed by measuring and analyzing only changes either in the main SPR peak angular position or in the reflection intensity at a fixed angle near the main SPR peak minimum.…”
Section: Introductionmentioning
confidence: 99%
“…First, the surface-immobilized receptor has restricted conformational flexibility for the analyte to access the entire binding sites [39], and thus may not retain its full solution-based activity [40]. In addition, avidity, in which the binding of analyte molecules with receptor molecules is synergistically stabilized by entropic effects [36], is known to have a noticeable contribution to high-affinity binding systems [41]. In our experiments, the presence of the solid surface may have led to reduced avidity effects because of less efficient diffusion [42] and limited clustering of analyte and receptor molecules [36].…”
Section: Resultsmentioning
confidence: 99%
“…We consider a monovalent model for the equilibrium affinity binding between the immobilized receptor (of concentration [ R ]) and the target analyte (of concentration [ A ]) to form a complex (of concentration [ RA ]) [36]: false[Rfalse]+false[Afalse]koffkonfalse[RAfalse] where k on and k off are the association and dissociation rate constants, respectively. The net rate of complex formation varies with time according to the following differential equation: dydt=konfalse[Afalse]false(ymaxyfalse)koffy where y and y max respectively represent the observed response signals respectively corresponding to the complex concentration [ RA ] and saturation complex concentration [ RA ] max (i.e., the asymptotic value of [ RA ] at infinite time) for a given concentration of injected analyte [ A ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation